2023
DOI: 10.3389/fbioe.2023.1119639
|View full text |Cite
|
Sign up to set email alerts
|

Implantation with SHED sheet induced with homogenate protein of spinal cord promotes functional recovery from spinal cord injury in rats

Abstract: Introduction: After spinal cord injury (SCI) occurs, the lesion is in a growth inhibitory microenvironment that severely hinders neural regeneration. In this microenvironment, inhibitory factors are predominant and factors that promote nerve regeneration are few. Improving neurotrophic factors in the microenvironment is the key to treating SCI.Methods: Based on cell sheet technology, we designed a bioactive material with a spinal cord‐like structure –SHED sheet induced with homogenate protein of spinal cord (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…On the 60th day post-SCI, a significantly greater recovery of motor function was observed compared to the control group and SHED suspension group (mean 8.20 ± 0.84 points for the hp-SHED group, mean 6.40 ± 1.14 points for the SHED suspension group, mean 3.20 ± 0.84 points for the control group, p < 0.001 for all comparisons). Similarly, SHED cells induced to differentiate with homogenate proteins of the spinal cord exhibited higher maximum grip strength values compared to all other study groups (mean 235.40 ± 27.93 g for the hp-SHED group, mean 173.00 ± 16.70 g for the SHED suspension group, mean 107.80 ± 14.81 g for the control group, p < 0.05 for all comparisons) [ 25 ]. Another study showed that co-culturing stem cell sheets formed from neuro-induced SHED with undifferentiated SHED resulted in more significant improvements in motor function scores in the grip strength test compared to single-type SHED cell sheets and the control group (mean 11.60 ± 1.14 points for the SHED + iSHED group, mean 7.60 ± 1.14 points for the SHED group, mean 2.60 ± 0.89 points for the control group, p < 0.001 for all comparisons) [ 22 ].…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…On the 60th day post-SCI, a significantly greater recovery of motor function was observed compared to the control group and SHED suspension group (mean 8.20 ± 0.84 points for the hp-SHED group, mean 6.40 ± 1.14 points for the SHED suspension group, mean 3.20 ± 0.84 points for the control group, p < 0.001 for all comparisons). Similarly, SHED cells induced to differentiate with homogenate proteins of the spinal cord exhibited higher maximum grip strength values compared to all other study groups (mean 235.40 ± 27.93 g for the hp-SHED group, mean 173.00 ± 16.70 g for the SHED suspension group, mean 107.80 ± 14.81 g for the control group, p < 0.05 for all comparisons) [ 25 ]. Another study showed that co-culturing stem cell sheets formed from neuro-induced SHED with undifferentiated SHED resulted in more significant improvements in motor function scores in the grip strength test compared to single-type SHED cell sheets and the control group (mean 11.60 ± 1.14 points for the SHED + iSHED group, mean 7.60 ± 1.14 points for the SHED group, mean 2.60 ± 0.89 points for the control group, p < 0.001 for all comparisons) [ 22 ].…”
Section: Resultsmentioning
confidence: 97%
“…Following the screening of titles and abstracts of identified articles, 16 articles were included as appropriate for the aim of this systematic review. After the full-text screening, 7 articles which were considered eligible according to inclusion and exclusion criteria, were finally included for qualitative analysis [ 22 , 25 30 ]. Nine records might appear to meet the inclusion criteria, but after full-text screening was finally excluded due to the following reasons: in vitro studies (3 articles); test group was cell aggregates (2 articles); non-English study (1 article); conference proceedings (2 articles) and duplicate study (1 article).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations